GENERATION-BASED CAREER DEVELOPMENT PATHWAYS: AN EFFORT TO OPTIMIZE THE PERFORMANCE OF GEN-Z EDUCATORS - Sabilil Muttaqin; Muhfidatul Nafila; Nofi Maria Krisnawati; Yazid Hady; Fatkhul Mubin; Putra Dian Kharisma Ivada (STAI ALHIKMAH Jakarta, 2026)
AbstractGeneration Zs, often labeled as